2019
DOI: 10.1001/jamanetworkopen.2019.0828
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reported Comparative Effectiveness and Safety of Atypical Antipsychotics in the Treatment of Behavioral and Psychological Symptoms of Dementia

Abstract: Key Points Question Which atypical antipsychotic is most beneficial and safe for the treatment of behavioral and psychological symptoms of dementia? Findings In this network meta-analysis of 17 studies (5373 patients), no significant differences were found across measures of effectiveness and safety among aripiprazole, olanzapine, quetiapine, and risperidone, although differences were found for some of these drugs and outcomes compared with placebo. No tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
125
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 82 publications
10
125
0
2
Order By: Relevance
“…Similar to two published NMAs of pharmacologic interventions in persons with dementia, we found that antipsychotics were associated with an increased risk of cerebrovascular events [30,31]. Although one of these NMAs included cholinesterase inhibitors, authors did not conduct analyses to assess for an association with mortality risk [30].…”
Section: Discussionsupporting
confidence: 69%
“…Similar to two published NMAs of pharmacologic interventions in persons with dementia, we found that antipsychotics were associated with an increased risk of cerebrovascular events [30,31]. Although one of these NMAs included cholinesterase inhibitors, authors did not conduct analyses to assess for an association with mortality risk [30].…”
Section: Discussionsupporting
confidence: 69%
“…Although antidepressants, particularly selective serotonin reuptake inhibitors, have fewer and less severe adverse effects than antipsychotic medications, treatment may still be complicated by cardiac conduction-delaying effects and effects on reducing agitation (40% response rate) are not evident until after 6 to 9 weeks of treatment. 6 Yunusa and colleagues 7 Downloaded From: https://jamanetwork.com/ on 10/01/2020 risperidone, and quetiapine over placebo was small and consistent with previous findings, further highlighting the need for more-effective behavioral and pharmacotherapies for BPSD.…”
supporting
confidence: 81%
“…Ultimately, 44 full texts of potentially relevant studies were independently assessed by two reviewers (GO, CB), and 10 were finally selected by agreement (see Supplemental material). [27][28][29][30][31][32][33][34][35][36] Medications showing evidence of benefit for the treatment of hyperactive delirium or other forms of agitation are reported in Table 1, along with other relevant clinical, pharmacological and regulatory data. Details on the search results, the study selection, the outcomes extracted from the selected reviews, the effect sizes and the strength of association are provided in the Supplement.…”
Section: Resultsmentioning
confidence: 99%